2018
DOI: 10.7547/16-024
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Kinematic Coupling Among the Rearfoot, Midfoot, and Forefoot Segments During Running and Walking

Abstract: Excessive rearfoot eversion during running is likely to lead to excessive midfoot dorsiflexion, and such abnormal kinematic coupling between the rearfoot and midfoot may be associated with mechanisms for the occurrence of injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Moreover, excessive rearfoot eversion angles exhibited during running would further result in excessive dorsiflexion of midfoot due to kinematic coupling. This abnormal foot motion has been proved to be a risk factor for lower limb RRI (Takabayashi et al, 2018). The above evidence clearly showed that the human foot is a particularly deformable and vulnerable structure during long-distance running.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Moreover, excessive rearfoot eversion angles exhibited during running would further result in excessive dorsiflexion of midfoot due to kinematic coupling. This abnormal foot motion has been proved to be a risk factor for lower limb RRI (Takabayashi et al, 2018). The above evidence clearly showed that the human foot is a particularly deformable and vulnerable structure during long-distance running.…”
Section: Introductionmentioning
confidence: 71%
“…As the primary interface of the lower limb with the external environment, the foot has been previously demonstrated to be a common injury site (Kindred et al, 2011;Zhou et al, 2019;Dempster et al, 2021). In addition, some foot biomechanical changes during running may further potentially increase the risk of RRI of the lower limbs (Mei et al, 2018;Takabayashi et al, 2018;Mei et al, 2019;Matias et al, 2020). For example, increased foot pronation during running would contribute to a significantly higher medical knee contact force, consequently increasing knee injury risks (Mei et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies investigated the relationship between physical activity and injuries, particularly those related to running [2,3]. Researches associating the behavior of the subtalar joint angle, specifically subtalar pronation, with the footwear used for running have significantly contributed to the comprehension of injuries involving the hip, knee, ankle and foot [4].…”
Section: Introductionmentioning
confidence: 99%
“…not on the ground, followed by a single limb support phase. This results in a difference in timing of events and muscular activation in the trunk and lower limb 18 . Kinematically, compared to walking, there is considerably more flexion in the foot joints during running where the limb acts in a more 'spring-like' fashion 17 .…”
mentioning
confidence: 99%
“…Kinematically, compared to walking, there is considerably more flexion in the foot joints during running where the limb acts in a more 'spring-like' fashion 17 . The kinematic coupling within the foot joints have also been found to be greater when running than walking 18 , namely there was more rearfoot eversion and forefoot dorsiflexion (arch deformation) in running than walking. Kinetically, the load taken by the feet increases from 1.2 times of bodyweight when walking to 2.5 times of bodyweight when running; the loading rate also increases from 8 times of bodyweight per second when walking to 30 times of bodyweight per second 19 .…”
mentioning
confidence: 99%